Pharmacotherapy of Lower Respiratory Tract Infections in Elderly—Focused on Antibiotics - Liu, Yang; Zhang, Yan; Zhao, Wanyu; Liu, Xiaolei; Hu, Fengjuan; Dong, Birong (Frontiers in Pharmacology, 2019)
Lower respiratory tract infections (LRTIs) refer to the inflammation of trachea, bronchi, bronchioles, and lung tissue. Old people have an increased risk of developing LRTIs compared to young adults. The prevalence of LRTIs in elderly population is not only related to underlying diseases and aging itself, but also to a variety of clinical issues, such as history of hospitalization, previous antibacterial therapy, mechanical ventilation, antibiotic resistance. These factors mentioned above have led to an increase in the prevalence and mortality of LRTIs in elderly, new medical strategies targeting LRTIs in this population are urgently needed. After a systematic review of the current randomized controlled trials and related studies, we recommend novel pharmacotherapies that demonstrate advantages for the management of LRTIs in people over the age of 65. We also briefly reviewed current medications for respiratory communicable diseases in elderly. Various sources of information were used to ensure all relevant studies were included. We searched Pubmed, MEDLINE (OvidSP), EMBASE (OvidSP), ClinicalTrials.gov. Strengths and limitations of these drugs were evaluated based on whether they have novelty of mechanism, favorable pharmacokinetic/pharmacodynamic profiles, avoidance of interactions and intolerance, simplicity of dosing, and their ability to cope with challenges which was mainly evaluated by the primary and secondary endpoints. The purpose of this review is to recommend most promising antibiotics for treatment of LRTIs in elderly (both in hospital and in the outpatient setting) based on the existing results of clinical studies with the novel antibiotics, and to briefly review current medications for respiratory communicable diseases in elderly, aiming to a better management of LRTIs in clinical practice.